1999
DOI: 10.1021/jm980551o
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Pharmacophore Model for the Design of EGFR Tyrosine Kinase Inhibitors:  Isoflavones and 3-Phenyl-4(1H)-quinolones

Abstract: Using a pharmacophore model for ATP-competitive inhibitors interacting with the active site of the EGFR protein tyrosine kinase together with published X-ray crystal data of quercetin (2) in complex with the Hck tyrosine kinase and of deschloroflavopiridol (3b) in complex with CDK2, a putative binding mode of the isoflavone genistein (1) was proposed. Then, based on literature data suggesting that a salicylic acid function, which is represented by the 5-hydroxy-4-keto motif in 1, could serve as a pharmacophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(71 citation statements)
references
References 30 publications
2
68
0
Order By: Relevance
“…The binding modes for ATP and erlotinib are also consistent with the existing pharmacophore model for ATP binding to kinases. 66,67,74 Significantly, a second binding mode, which has a higher affinity to the mutant kinase L834R, is revealed in our calculations. This mode still blocks the ATP binding pocket and in addition shows an additional interaction between erloitnib and the R834 residue.…”
Section: Constitutive Activation Of the L834r Mutantsupporting
confidence: 49%
“…The binding modes for ATP and erlotinib are also consistent with the existing pharmacophore model for ATP binding to kinases. 66,67,74 Significantly, a second binding mode, which has a higher affinity to the mutant kinase L834R, is revealed in our calculations. This mode still blocks the ATP binding pocket and in addition shows an additional interaction between erloitnib and the R834 residue.…”
Section: Constitutive Activation Of the L834r Mutantsupporting
confidence: 49%
“…These findings suggested that 1 induced cell death not only by direct action on IGF-I-dependent pathway but also involves other action mechanism. Although, some kinase inhibitors of IGF-IR were reported [8,9], there is only one report that synthetic quinolones possessed inhibitory effects against EGFR tyrosine kinase [10]. Quinolones are reported to show antitumor effects targeting DNA related factors such as topoisomerases I and II [11ϳ15].…”
mentioning
confidence: 99%
“…They play important roles in the plant reproduction and defense and also possess a wide range of biological and pharmaceutical activities. anticonvulsive, 4 α-glucosidase inhibitor, 5 aldehyde dehydrogenase ALDH-2 inhibitor, 6 EGFR tyrosine kinase 7 and COX-2 inhibiting activity. 8 The group of 2-and 3-styrylchromones is a smaller family of chromonoids 9,10 but few representatives are known in the nature and their biological activities were also reported and reviewed.…”
Section: Introductionmentioning
confidence: 99%